2023
DOI: 10.3389/fcimb.2023.1159822
|View full text |Cite
|
Sign up to set email alerts
|

Insights into oral microbiome and colorectal cancer – on the way of searching new perspectives

Abstract: Microbiome is a keystone polymicrobial community that coexist with human body in a beneficial relationship. These microorganisms enable the human body to maintain homeostasis and take part in mechanisms of defense against infection and in the absorption of nutrients. Even though microbiome is involved in physiologic processes that are beneficial to host health, it may also cause serious detrimental issues. Additionally, it has been proven that bacteria can migrate to other human body compartments and colonize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
(77 reference statements)
0
0
0
Order By: Relevance
“…Researchers have found that oral bacteria can migrate to the colon through the bloodstream or oral-gut axis, leading to pathogenesis. [ 42 ] However, our study found no causal relationship between periodontal diseases and GC, which is partially consistent with the prospective study by Ndegwa et al [ 43 ] Their research showed that higher levels of dental plaque do not significantly increase the risk of GC, and that the relationship between periodontal diseases and GC is largely confounded by age. Porphyromonas gingivalis , one of the major pathogenic bacteria in periodontal diseases, can survive in the oral cavity and contribute to the development of malignant tumors.…”
Section: Discussionsupporting
confidence: 92%
“…Researchers have found that oral bacteria can migrate to the colon through the bloodstream or oral-gut axis, leading to pathogenesis. [ 42 ] However, our study found no causal relationship between periodontal diseases and GC, which is partially consistent with the prospective study by Ndegwa et al [ 43 ] Their research showed that higher levels of dental plaque do not significantly increase the risk of GC, and that the relationship between periodontal diseases and GC is largely confounded by age. Porphyromonas gingivalis , one of the major pathogenic bacteria in periodontal diseases, can survive in the oral cavity and contribute to the development of malignant tumors.…”
Section: Discussionsupporting
confidence: 92%